SASSANG IN COMMUNITY LIFE IN BALLA VILLAGE, BALLA DISTRICT, MAMASA REGENCY - Milani Nurdin; Muhammad Zulfadli; Hasni Hasni (UNM Geographic Journal, 2022)
This study aims to (1) find out how the factors that influence the reduced public interest in making Sassang in Balla Village, Balla District, Mamasa Regency. (2) To find out what strategies were used to maintain the making of Sassang in Balla Village, Balla District, Mamasa Regency. The type of research carried out was qualitative research using a descriptive approach. Data was collected by means of observation, interviews, and documentation. The data analysis techniques used are data collection, word reduction, data presentation, and drawing conclusions/verification. Based on the results of the study, it shows that (1) the factors that influence the lack of public interest in making Sassang in Balla Village, Balla District, Mamasa Regency, consist of several factors, namely lack of understanding, many people wandering, lack of love, and lack of awareness to preserve culture. (2) The strategy that can be taken by the community to maintain the making of Sassang in Balla Village, Balla District, Mamasa Regency is to increase the conservative and progressive power, build cultural awareness and cultural resilience in the community, strengthen and strengthen identity and identity.